ASSOCIATION BETWEEN PSORIASIS AND DEMENTIA: A SYSTEMATIC REVIEW - Magdalena Domisiewicz; Kacper Domisiewicz (International Journal of Innovative Technologies in Social Science, 2025)
Background: Psoriasis is a chronic immune-mediated skin disease characterized by systemic inflammation, while dementia, including Alzheimer’s disease (AD) and vascular dementia, is increasingly recognized as an inflammatory neurodegenerative condition. Both disorders share common risk factors such as age, cardiovascular comorbidity, and metabolic disease. Whether psoriasis independently increases dementia risk remains unclear.Objectives: To systematically evaluate the epidemiologic association between psoriasis and dementia, explore potential causality using genetic approaches, and assess the impact of systemic therapies, particularly biologics, on cognitive outcomes.Methods: Following PRISMA guidelines, PubMed was searched for studies published between 2013 and 2025. Eligible studies included observational cohorts, case-control analyses, and Mendelian randomization studies examining dementia outcomes in patients with psoriasis. Data extraction was performed independently by two reviewers.Results: Epidemiologic evidence from Taiwan, Korea, Denmark, and the UK suggests a modestly increased risk of dementia in psoriasis (odds ratios 1.10–1.25), with higher estimates in younger patients and for vascular subtypes. However, findings were inconsistent, with some cohorts reporting null or protective associations. Notably, systemic and biologic therapies were consistently associated with reduced dementia incidence. Mendelian randomization studies found no genetic evidence supporting psoriasis as a causal risk factor for AD, suggesting shared inflammatory and vascular pathways rather than direct causality.Conclusions: Psoriasis may modestly increase dementia risk through systemic inflammation and comorbid vascular disease, rather than genetic liability. Systemic therapies, particularly biologics targeting TNF-α and IL-12/23, may confer neuroprotective benefits. Further prospective studies are warranted to clarify causality and therapeutic implications.